Induction and characterization of extracellular traps by gilthead seabream (Sparus aurata L.) head-kidney leucocytes. Issue 130 (November 2022) - Albaladejo-Riad, Nora; Cuesta, Alberto; Esteban, M. Ángeles
Abstract: The aim of this study was the induction and characterization of extracellular traps (ETs) produced by gilthead seabream ( Sparus aura ta L.) head-kidney leucocytes. The cells were incubated several times (10, 30, 60, 120, and 180 min) with different concentrations of the stimulants diluted in RPMI-1640 culture medium: RPMI-1640 (control), β-glucan from Saccharomyces cerevisiae (BG, 0–400 μg mL −1 ), lipopolysaccharide from Escherichia coli (LPS, 0–10 μg mL −1 ), calcium ionophore A23187 (CaI, 0–5 μg mL −1 ), Phorbol 12-myristate 13-acetate (PMA, 0–1000 ng mL −1 ) and polyinosinic–polycytidylic acid sodium salt (Poly I:C, 0–200 μg mL −1 ). BG, LPS and CaI exerted only weak stimulatory activity, while PMA and poly I:C exerted a potent one. After stimulation of the leucocytes, ETs structures were quantified and visualised through staining of the chromatin with nucleic acid-specific dyes and immunocytochemical probing of characteristic proteins expected to decorate the structure. ETs structures had DNA and myeloperoxidase. The ETs morphology was studied by light and scanning electron microscopy. These data confirm that seabream leucocytes form ETs with different morphological properties, depending on the used stimulant. These results will be the basis for new studies to analyse the implication of this mechanism in fish immunity. All this new knowledge will have its application in fish farms when we learn to manipulate the innate immune response in order to mitigate microbial infections. Graphical abstract: Image 1